2019
DOI: 10.1007/s13202-019-00805-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of maximum likelihood sparse spike inversion and probabilistic neural network for reservoir characterization: a study from F-3 block, the Netherlands

Abstract: Maximum likelihood sparse spike inversion (MLSSI) method is commonly used in the seismic industry to estimate petrophysical parameters in inter-well region. In present study, maximum likelihood sparse spike inversion technique is applied to the processed 3D post-stack seismic data from the F-3 block, the Netherlands, for estimation of acoustic impedance in the region between the wells. The analysis shows that the impedance varies from 2500 to 6200 m/s/*g/cc in the region which is relatively low and indicates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 32 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Previous research has already shown that reservoir porosity and density can be measured using statistical methods and intelligent systems [10,[31][32][33]. However, the majority of the time, neural network techniques rely on a linear fit between seismic features and reservoir properties [34][35][36][37]. This paper aims to use seismic attributes to estimate petrophysical parameters from well-log data by applying PNN and MLFN neural network techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has already shown that reservoir porosity and density can be measured using statistical methods and intelligent systems [10,[31][32][33]. However, the majority of the time, neural network techniques rely on a linear fit between seismic features and reservoir properties [34][35][36][37]. This paper aims to use seismic attributes to estimate petrophysical parameters from well-log data by applying PNN and MLFN neural network techniques.…”
Section: Introductionmentioning
confidence: 99%